Pemberdayaan Masyarakat Berbasis Masjid (Optimalisasi Dana Menganggur Pada Masjid-Masjid Di Kota Jambi) - Dhea Indriani; Addiarrahman Addiarrahman; Muhammad Subhan (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
This thesis aims to determine the implementation of mosque-based community empowerment in the city of Jambi (Study of mosques in the Telanaipura sub-district and the mosque in the Danau Teluk sub-district). In this study the authors used qualitative analysis methods, where primary data was obtained from interviews and secondary data obtained from documentation. The places in this study were the Ar-Raudho mosque, the Abu Bakar Sari mosque, the Ikhsaniyyah mosque and the Nurul Islam mosque. The actors in this study were mosque administrators and the community. The results of this study indicate that of the several mosques that the authors examined, there are similarities and differences, namely the similarities are from the activities of the mosques, which are the same, while the differences from several mosques are from the form of empowerment.